Exhaustion of Airway Basal Progenitor Cells in Early and Established Chronic Obstructive Pulmonary Disease - Ghosh, Moumita; Miller, York E.; Nakachi, Ichiro; Kwon, Jennifer B.; Barón, Anna E.; Brantley, Alexandra E.; Merrick, Daniel T.; Franklin, Wilbur A.; Keith, Robert L.; Vandivier, R. William (American Journal of Respiratory and Critical Care Medicine, 2018)
Up to 40% of smokers develop chronic obstructive pulmonary disease (COPD) over a period that spans decades. Despite the importance of COPD, much remains to be learned about susceptibility and pathogenesis, especially during early, prediagnostic stages of disease. Airway basal progenitor cells are crucial for lung health and resilience because of their ability to repair injured airways. In COPD, the normal airway epithelium is replaced with increased basal and secretory (mucous) cells and decreased ciliated cells, suggesting that progenitors are impaired. To examine airway basal progenitor cells and lung function in smokers with and without COPD. Bronchial biopsies taken from smokers at risk for COPD and lung cancer were used to acquire airway basal progenitor cells. They were evaluated for count, self-renewal, and multipotentiality (ability to differentiate to basal, mucous, and ciliated cells), and progenitor count was examined for its relationship with lung function. Basal progenitor count, self-renewal, and multipotentiality were all reduced in COPD versus non-COPD. COPD progenitors produced an epithelium with increased basal and mucous cells and decreased ciliated cells, replicating the COPD phenotype. Progenitor depletion correlated with lung function and identified a subset of subjects without COPD with lung function that was midway between non-COPD with high progenitor counts and those with COPD. Basal progenitor dysfunction relates to the histologic and physiologic manifestations of COPD and identifies a subset that may represent an early, prediagnostic stage of COPD, indicating that progenitor exhaustion is involved in COPD pathogenesis.